The Existence of Indigenous Youth on the Credibility of Customary Law Instruments - Tjahjani, Joejoen; M. Yanto; Rupawanti, Nadia (Universitas Islam Lamongan, 2024)
ABSTRACT At the regional level, the government's commitment to the formation of Regional Regulations on the recognition of indigenous peoples as one of the customary law instruments is still low, customary law instruments should be able to form binding forces and provide justice for indigenous peoples. In this case, the existence of indigenous youth is urgently needed in decision-making and their dedicated efforts in climate action, the search for justice, and the creation of intergenerational relationships that preserve their culture and traditions. Indigenous youth are very strategic in mapping customary territories, advocating for policies and succeeding in the management of customary territories based on the culture and wisdom traditions of indigenous peoples. The existence of indigenous youth as the next generation greatly determines the credibility of customary law instruments.